2018
DOI: 10.1186/s40249-017-0384-1
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of dengue among healthy adults in a rural community in Southern Malaysia: a pilot study

Abstract: BackgroundThe frequency and magnitude of dengue epidemics continue to increase exponentially in Malaysia, with a shift in the age range predominance toward adults and an expansion to rural areas. Despite this, information pertaining to the extent of transmission of dengue virus (DENV) in the rural community is lacking. This community-based pilot study was conducted to establish DENV seroprevalence amongst healthy adults in a rural district in Southern Malaysia, and to identify influencing factors.MethodsIn thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 20 publications
10
80
0
Order By: Relevance
“…Approximately 96.8% of the IgG ELISA-positive serum samples contained DENV-neutralising antibodies. This is similar to the results of a recent study in Malaysia where the Panbio IgG Indirect ELISA had a specificity of 100% compared with a neutralisation test [24].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Approximately 96.8% of the IgG ELISA-positive serum samples contained DENV-neutralising antibodies. This is similar to the results of a recent study in Malaysia where the Panbio IgG Indirect ELISA had a specificity of 100% compared with a neutralisation test [24].…”
Section: Discussionsupporting
confidence: 90%
“…The high seroprevalence in Port Sudan indicates an almost universal exposure to dengue viruses. The seroprevalence in this town was comparable to that in the South Indian state Tamil Nadu and in several countries in Southeast Asia . The seroprevalence was higher than in other countries in Africa and in the Middle East .…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Although it is widely known that there is cross-reactivity among flaviviruses, ELISA is still the most affordable -hence most commonly used -test (24). Since YFV vaccination is an expected cause of cross-reactions, we performed PRNT for DENV and YFV in a subset of samples, and found that the congruence between DENV ELISA and PRNT was lower than in American and Asian settings (33)(34)(35)(36)(37). A similar observation was made in another study in DRC with a certain level of discordance between ELISA and PRNT (38), and in a study in Ethiopia where crossreaction and low confirmation by PRNT was also shown (39).…”
Section: Resultsmentioning
confidence: 99%
“…Our findings suggest that high density, urbanised areas are not necessarily the primary drivers of ongoing epidemics in Sabah, and that factors other than population size may drive the risk in rural areas. Recent studies in other areas of Malaysia have also shown that dengue infection can occur at equivalent rates in both rural and urban areas (37, 38). It could be that the threshold human density required to maintain transmission may be lower than previously thought, although human movement (which may relate to population density) between urban and rural areas is also likely to have influenced the patterns we observed (39, 40).…”
Section: Discussionmentioning
confidence: 97%